THE HABIT OF USING HAND SANITIZER AMONG TEENAGERS AND ITS EFFECTIVENESS COMPARED TO WASHING HANDS – A LITERATURE REVIEW - Belgis, Belgis; Fatmalouisa Algadrie, Zahrah (Universitas Airlangga, 2024)
Introduction: The spread of infectious diseases occurs when disease-causing agents, such as bacteria, viruses, or germs move and infect from one person to another. Teenage is a phase that is very vulnerable to contracting infectious diseases because it is at a stage of physical development, emotional changes, and increased social relationships. One practical way to prevent infectious diseases is to kill disease-causing agents by washing hands. However, its use is often replaced with a more realistic hand sanitizer. For this reason, this research will compare the efficacy of hand sanitizers and hand washing specifically among teenage populations. Methods: This research is a literature study that uses secondary data from publications published in 2007-2024 and is relevant to the topic of discussion. Of the 16,800 articles according to keywords, 8 articles were found that met the criteria for further discussion. Results: The results of the eight journals selected according to the requirements showed that 3 journals stated that using hand sanitizer was more effective than washing hands. Meanwhile, 5 other journals stated that washing hands was more effective than hand sanitizer. Because, there are still remaining germs, bacteria, and viruses stuck to the hands. Moreover, hand sanitizers are not able to clean the deepest layers of the skin, and long-term use also makes the skin dry and irritated because hand sanitizers contain quite high amounts of alcohol. Conclusions: For this reason, teenagers are expected to prioritize washing their hands with soap and running water rather than using hand sanitizer.